Citrus Diseases Exotic to Florida: Citrus Yellow Mosaic - Kuang-Ren Chung; Ronald H. Brlansky (EDIS)
Citrus yellow mosaic is an important viral disease in India, where it causes significant yield reduction. In some groves, infection rate may be as high as 70%. CYMV induces a bright yellow mottling or vein flecking that persists in mature leaves. Yields are sharply reduced in chronically infected 'Sathgudi' sweet orange trees in India, and fruit may also show mosaic symptoms. This 2-page fact sheet was written by K.-R. Chung and R. H. Brlansky, and published by the UF Department of Plant Pathology, February 2012.